Development of stock exchange in Myanmar - Kyaw Zay Yar Bo; Supasith Chonglerttham; Islam, Nazrul; Donyaprueth Krairit; Ministry of Foreign Affairs, Norway (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
The purpose of this paper is to analysis the success factors of stock markets in A SEAN and the development of stock exchange in Myanmar. After the changes of government in Myanmar in 2010, the main duty of the newly government is to reduce the poverty level of the country. The changes of the newly government get international attentions and Myanmar became the Asia {u2019}s last frontier for the investors. The lack of proper ways for investment in Myanmar is one of the reasons for the countries poor economy. To solve this problem, Myanmar government decided to establish a stock exchange not later than 2015. This paper use the data from the World Bank to analysis the success factors of the stock exchanges in ASEAN countries. From the analysis results, several factors that have relations with the success of their stock markets are highlighted and the most suitable country that can be an example for the development of stock exchange in Myanmar is discussed
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Project (M.B.A.) - Asian Institute of Technology, 2014
Keywords: Stock exchanges -- Myanmar